2013
DOI: 10.1080/0267257x.2013.796322
|View full text |Cite
|
Sign up to set email alerts
|

Developing brand champions: A franchisee perspective

Abstract: The establishment of a compelling brand lies at the heart of a franchise network's success. To maintain brand integrity, franchisors rely on franchisees to deliver the brand promise consistently. However, franchisee behaviour is sometimes difficult to manage, impacting negatively on the franchise brand. In adopting an internal brand management theoretical lens, this study provides new insight into the development of franchisees as brand champions. This is achieved through the empirical validation of a model, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…Implications for Management King et al (2013) find that during an economic downturn, an employee's opportunity to leave the firm may be limited. Service industry managers face a barrage of cost saving initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Implications for Management King et al (2013) find that during an economic downturn, an employee's opportunity to leave the firm may be limited. Service industry managers face a barrage of cost saving initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this work has shown that franchises should invest in building a supportive IM culture, if they are interested in developing a positive and collaborative environment, with continuously harmonious win-win exchanges between franchisor and franchisee. Thus, the IM culture will help motivate franchisees to respond positively to the franchise and to ensure their willingness to continue the relationship for the long term (King et al, 2013).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The key to its success is based on the development of quality relationships between franchisor and franchisees, which is why the literature continues to emphasize the need for further study (e.g., Altinay et al, 2014a). In fact, there is a recent research trend that reinforces the idea that beyond the mere contractual exchange between the parties, the franchise has an important relational dimension (Fern andez-Monroy and Meli an-Alzola, 2005;King et al, 2013;Lee et al, The relationship between IM culture and training relevance Various authors in the IM literature point out the need for a value system to guide the company in developing behaviours that meet the needs of its employees, and ultimately lead to greater value to the customer (Lings, 2004;Lings and Greenley, 2005;Gounaris, 2006;Gounaris et al, 2010). This value system represents the cultural aspect of IM by considering people to be the organization's most valuable asset, which can influence satisfaction and loyalty of this key resource (Lings and Greenley, 2005;Peltier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In line with RCT, the introduction and positioning of organizational relationship quality in the conceptual model, implies mediation. Based on the contention of King et al, (2013) that organizationally based relational considerations are the key to determining the strength and valence of the association between organizationally generated antecedents and employee centred outcome variables, the mediation hypothesis is supported. We argue that the organization's support mechanisms (i.e.…”
Section: Hypothesesmentioning
confidence: 99%